Percutaneous endoluminal arterial cryoenergy improves vascular remodelling after angioplasty - Tanguay, Jean-François; Geoffroy, Pascale; Dorval, Jean-François; Sirois, Martin G. (Thrombosis and Haemostasis, 2004)
This study aimed to investigate the effect of percutaneous endoluminal arterial cryoenergy immediately after balloon angioplasty on vascular remodeling. Restenosis, the main complication after coronary artery angioplasty, is a complex phenomenon in which vascular remodeling plays a prominent role. Observations of reduced scarring in freeze-induced wounds suggest potential value for cryoenergy in the prevention of restenosis. Juvenile swine underwent a first oversized balloon injury in both carotid arteries (CA) (3 injury sites/artery) and a second injury at day 14. At that time, one CA was randomly assigned to endoluminal cryoenergy of the sequential segments (proximal, medial, distal) at −15ºC, −30ºC, and −50ºC for 120 sec, and the other CA was used as control. Animals were sacrificed 28 days after the second procedure. Compared with intact reference segments, angioplasty reduced both the luminal (LA) and the external elastic lamina (EEL) areas from 6.66±0.59 to 3.13±0.54 mm2 (p<0.05) and from 8.81±0.81 to 6.48±0.52 mm2 (p<0.05), respectively. Cryoenergy, at the temperature with maximal benefits (-50°C), caused a temperature-related protection, as the LA was maintained (6.79±0.89 versus 7.18± 0.78 mm2 for reference) and the EEL area increased from 9.12±0.78 to 12.98±1.07 mm2, p<0.05. Moreover, cryoenergy increased the density of collagen III (p<0.05) which correlated with the maintenance of the LA (r=0.8045, p<0.009). Cryoenergy prevents late luminal loss after double-injury angioplasty by improving vascular remodeling, and is an interesting new therapeutic approach for the prevention of restenosis after angioplasty. The increased synthesis of collagen III appears to be involved in this phenomenon and could be a potential method of stabilizing the vulnerable plaque.
Keywords: Angioplasty; remodeling; restenosis; cryoenergy; collagen